Confidence as a social imperative and value of constitutional development - Karpovich, Natallia A. (Journal of the Belarusian State University. Law, 2026)
The author of the article examines the importance of maintaining public confidence in the state and law as a crucial factor for the sustainability of constitutional and legal development. Features of formation and manifestation of confidence in constitutional and legal relations are identified. The author analyses the acts of the Constitutional Court of the Republic of Belarus, in which the constitutional principle of citizens’ confidence in the government institutions and the legal system is justified, its general social aspects and the role of confidence as an element of applicable law are highlighted, the appropriate development of legislative mechanisms that contribute to the progressive building of public confidence is pointed out. The conclusion is made that the Constitution of the Republic of Belarus as a fundamental social contract actualises the value of confidence, establishes appropriate requirements for state officials, activities of state bodies and serves as the basis for legal mechanisms, aimed at maintaining public confidence.
Keywords: Constitution of the Republic of Belarus; confidence; constitutional development; Constitutional Court of the Republic of Belarus; state bodies; law making; law enforcement